Ionic liquid-facilitated synthesis and catalytic activity of highly dispersed Ag nanoclusters supported on TiO2 - Zhang, H.; Li, Xin Yong; Chen, G. (The Royal Society of Chemistry, 2009)
This study describes a one-pot sol-gel method for the synthesis of Ag/TiO2 nanocomposite powders. TEM images showed that the Ag clusters formed with this method are highly dispersed on the surface of TiO2 nanoparticles. UV/visible spectroscopy results indicated that [BMIM][PF 6], an imidazolium-based room-temperature ionic liquid, strongly inhibited the formation and growth of Ag clusters in N,N-dimethylformamide (DMF) solvent. This made it possible to prepare a stable stock solution containing AgNO3-[BMIM][PF6]-DMF. Dilution of the stock solution followed by hydrolysis resulted in a gel that was processed to produce Ag/TiO2 nanocomposites containing Ag clusters with average size smaller than 3 nm. XPS results indicated that the silver species exist predominantly in the metallic form. Because of the high dispersion and controlled size of the Ag clusters, the Ag/TiO2 nanocomposites demonstrated excellent catalytic performance in the aqueous phase reduction of methylene blue and the hydrogenation of 4-nitrophenol using NaBH4 as the reducing agent. © 2009 The Royal Society of Chemistry.